Methylation Analysis of Colitis-Associated Colorectal Carcinomas. - Haumaier, Franziska; Dregelies, Theresa; Sterlacci, William; Atreya, Raja; Vieth, Michael (Discovery medicine, 2024)
BACKGROUND: Ulcerative colitis is a well-known inflammatory bowel disease. Patients have an increased risk of developing colitis associated carcinoma (CAC). It is important for patient management to be able to distinguish between ulcerative colitis associated carcinoma and sporadic carcinoma (sCRC). However, this distinction is frequently very challenging. It is not readily possible to differentiate this histologically. However, the diagnosis is crucial for the patient's further treatment and follow-up. An attempt was therefore made to develop a diagnostic regime that would enable a reliable distinction between sCRC and CAC. METHODS: We screened 96 patients analyzing more than 850,000 methylation hotspots, to detect distinct epigenetic patterns between both types of carcinomas. Patients with sporadic carcinoma and colitis-associated carcinoma as well as patients with normal colon and patients with confirmed ulcerative colitis without neoplasia were used for the analysis. By extensively filtering the results, methylation sites relevant to distinguish between CAC and sCRC were identified. RESULTS: After the results were filtered, three methylation sites relevant to distinguish between CAC and sCRC were identified. For this purpose, methylation limit values were defined, which favor the samples as CAC or sCRC up to a certain methylation value of the methylation sites. The combination of three methylation sites allows a correct assignment to CAC or sCRC in 94.5% of the cases. CONCLUSION: The results show that these three methylation sites are promising markers in the diagnosis of CAC vs sCRC. Nevertheless, the diagnosis should always be made in conjunction with histomorphological analyses.
EVALuna2:591089